Intramethod Comparability: The Case of the Oil and Gas Industry. - Lilien, Steven; Pastena, Victor (The Accounting Review, 1981)
Abstract ABSTRACT: A unique opportunity to investigate intramethod comparability arose recently when the Securities and Exchange Commission specified the procedures that must be followed by oil and gas producers accounting for exploratory costs under either the full cost or the successful efforts method. Although the Commission did not mandate which method registrants must use, it did define the specific applications to be followed under each method. Similarly, it required registrants to disclose the impact of retroactive application of the procedures on retained earnings and current net income. These adjustments provide a means to measure the magnitude of intramethod accounting differences that existed in the oil and gas industry before uniform applications were imposed. Results demonstrate that the choice of specific procedures within a supposed accounting method can have a material effect on net income, retained earnings, and asset balances. These results imply that intramethod uniformity can be vital in achieving the goal of intraindustry comparability of financial statements.